(untitled) (Research, Society and Development, 2022)
This article aims to highlight the importance of school lunches for students of a municipal elementary school in the municipality of Sapucaia, located in the Southeast region of the State of Pará. For this, documentary research was carried out, collecting data in documents made available by the municipality related to the food offered, in order to analyze the nutritional status of students and the acceptance of school lunches. Through nutritional analysis, it was observed that 52.4% of students fit the categorization called eutrophic, that is, they have normal weight for their age, height and gender, however, 42.9% found on the index of obesity and overweight. On the other hand, with regard to the underweight group, the percentage was 4.8%. The level of acceptance of the meal offered revealed that 92% of the students declared their total satisfaction both with the quality of the food and the types of ingredients served in the lunch, 6% classified the meal as regular and another 2% showed total dissatisfaction. Based on the results obtained, it was possible that the supply of food during school periods meets expectations even in the face of difficulties encountered regarding the supply of qualified products from family farming due to the unpreparedness and disorganization of many local rural producers and with regard to the diagnosis nutritional value, the sum of students with obesity and overweight is a warning sign due to the growing number of children and adolescents with diseases resulting from obesity.